Insights into the genome of Methylobacterium sp. NMS14P, a novel bacterium for growth promotion of maize, chili, and sugarcane - Jirakkakul, Jiraporn; Khoiri, Ahmad Nuruddin; Duangfoo, Thanawat; Dulsawat, Sudarat; Sutheeworapong, Sawannee; Petsong, Kantiya; Wattanachaisaereekul, Songsak; Paenkaew, Prasobsook; Tachaleat, Anuwat; Cheevadhanarak, Supapon; Prommeenate, Peerada (PloS one, 2023)
A novel methylotrophic bacterium designated as NMS14P was isolated from the root of an organic coffee plant ( Coffea arabica ) in Thailand. The 16S rRNA sequence analysis revealed that this new isolate belongs to the genus Methylobacterium , and its novelty was clarified by genomic and comparative genomic analyses, in which NMS14P exhibited low levels of relatedness with other Methylobacterium- type strains. NMS14P genome consists of a 6,268,579 bp chromosome, accompanied by a 542,519 bp megaplasmid and a 66,590 bp plasmid, namely pNMS14P1 and pNMS14P2, respectively. Several genes conferring plant growth promotion are aggregated on both chromosome and plasmids, including phosphate solubilization, indole-3-acetic acid (IAA) biosynthesis, cytokinins (CKs) production, 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity, sulfur-oxidizing activity, trehalose synthesis, and urea metabolism. Furthermore, pangenome analysis showed that NMS14P possessed the highest number of strain-specific genes accounting for 1408 genes, particularly those that are essential for colonization and survival in a wide array of host environments, such as ABC transporter, chemotaxis, quorum sensing, biofilm formation, and biosynthesis of secondary metabolites. In vivo tests have supported that NMS14P significantly promoted the growth and development of maize, chili, and sugarcane. Collectively, NMS14P is proposed as a novel plant growth-promoting Methylobacterium that could potentially be applied to a broad range of host plants as Methylobacterium -based biofertilizers to reduce and ultimately substitute the use of synthetic agrochemicals for sustainable agriculture.